Penyuluhan dan Penguatan Literasi Ramah Lingkungan dalam Pengelolaan Sampah Rumah Tangga di Desa Karanganom Kandeman Batang - Setiawan, Hendy; Maulani, Wihda (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
The purpose of this paper is to describe the waste management outreach conducted in Kranganom Kandeman Village, Batang. Waste management issues in Batang Regency still face serious challenges. This is triggered by low waste management literacy, the unequal distribution of waste management systems, and limited funds allocated for waste management. Therefore, this situation requires all parties to participate in responding to the waste issue, including villages. This community service method was carried out using outreach in Karanganom Village. The results of the outreach show that many public facilities in the village still do not have waste disposal sites. Furthermore, waste management literacy in the community is still quite inadequate. Therefore, this outreach is considered to have an impact on increasing community literacy, especially the village as a stakeholder.